Should the processus vaginalis sac be opened or closed in pediatric herniotomy?: a two-center cohort study - Michler, Veronika; Elrod, Julia; Wingtes, Kristofer; Trah, Julian; Reinshagen, Konrad; Boettcher, Michael (Pediatric surgery international, 2022)
Inguinal hernia repair is one of the most common operations in children. To improve outcome, several techniques are used. However, it has not been established if the open or the closed hernia sac preparation technique is superior in (premature) neonates and older children.
Gesehen am 24.10.2023